Optimizing the Utilization of Development Funds for the Prosperity of Rural Communities in South Sumatra - Suatmiati, Sri; Mahfuz, Abdul Latif (Technium Social Sciences Journal, 2022)
The Village Fund is a fund sponsored by the government that aims to strengthen village communities so that the village economy and education can be improved as a whole. Optimization is an effort that is carried out optimally in accordance with the designation stipulated by government regulations. This study aims to determine the application of positive laws governing village funds in order to improve the prosperity of the people of South Sumatra. To achieve this goal, the writer conducted normative and empirical research, which made the system of legal norms as a study material and was associated with legal events. In this study the data used were secondary data, secondary data consists of primary legal materials containing statutory regulations and secondary legal materials that were the results of legal research, journals, books and related scientific works. Literature studies and field studies were used as techniques in obtaining data, and processed using descriptive analysis methods to obtain conclusions. The results of the study showed that there were differences in the various villages in South Sumatra in the use of village funds, so that a new policy is needed that can guarantee the use of village funds for prosperity so that the use of village development funds can be directed and have clearer uses which have an impact on the prosperity of rural communities, especially in South Sumatra.